The Arabidopsis Nodulin Homeobox Factor AtNDX Interacts with AtRING1A/B and Negatively Regulates Abscisic Acid Signaling. Issue 3 (9th January 2020) - Zhu, Yujuan; Hu, Xiaoying; Duan, Ying; Li, Shaofang; Wang, Yu; Rehman, Amin Ur; He, Junna; Zhang, Jing; Hua, Deping; Yang, Li; Wang, Li; Chen, Zhizhong; et al.
Abstract : Arabidopsis nodulin homeobox protein AtNDX interacts with the Polycomb Repressive Complex 1 (PRC1) core components AtRING1A and AtRING1B and negatively regulates ABI4 expression during ABA signaling. Abstract: The phytohormone abscisic acid (ABA) and the Polycomb group proteins have key roles in regulating plant growth and development; however, their interplay and underlying mechanisms are not fully understood. Here, we identified an Arabidopsis ( Arabidopsis thaliana ) nodulin homeobox (AtNDX) protein as a negative regulator in the ABA signaling pathway. AtNDX mutants are hypersensitive to ABA, as measured by inhibition of seed germination and root growth, and the expression of AtNDX is downregulated by ABA. AtNDX interacts with the Polycomb Repressive Complex1 (PRC1) core components AtRING1A and AtRING1B in vitro and in vivo, and together, they negatively regulate the expression levels of some ABA-responsive genes. We identified ABA - INSENSITIVE ( ABI4 ) as a direct target of AtNDX. AtNDX directly binds the downstream region of ABI4 and deleting this region increases the ABA sensitivity of primary root growth. Furthermore, ABI4 mutations rescue the ABA-hypersensitive phenotypes of ndx mutants and ABI4 -overexpressing plants are hypersensitive to ABA in primary root growth. Thus, our work reveals the critical functions of AtNDX and PRC1 in some ABA-mediated processes and their regulation of ABI4 .